Autonomous Maritime Logistics in the Age of Sustainable Digital Transformation: An Integrative Framework for Smart and Green Shipping - Weda, Iwan (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
The maritime logistics sector is undergoing a profound transformation driven by the convergence of automation, digitalization, and sustainability imperatives. This paper explores the emerging paradigm of autonomous maritime logistics within a sustainable digital framework, addressing both technological and regulatory dimensions. Using a multidisciplinary lens combining systems theory, environmental economics, and maritime informatics, this study synthesizes recent empirical findings and proposes a conceptual model integrating autonomous technologies with environmental and operational performance indicators. The novelty of this research lies in its articulation of a sustainable-autonomous symbiosis as the future backbone of maritime logistics infrastructure. The study also offers policy and managerial recommendations for fostering resilient and intelligent maritime supply chains.